Influence of medium and method on the in vitro susceptibility of Pseudomonas aeruginosa and other bacteria to ciprofloxacin and enoxacin. - Blaser, J (1986)
Ciprofloxacin and enoxacin were two- to fourfold less active against Pseudomonas aeruginosa in calcium- and magnesium-supplemented broth compared with unsupplemented broth regardless of inoculum size, presence of serum, or use of inhibitory or bactericidal endpoints (P less than 0.01). The effect of cation supplementation was less pronounced and less consistent for Escherichia coli, Klebsiella pneumoniae, and Staphylococcus aureus.